The Relationship between Chinese Men and Indigenous Women in Gowok (1929): Postcolonial Feminist Studies - Susanto, Dwi (Universitas Airlangga, 2023)
This study aims to analyse how a Chinese-Indonesia descent male author represented indigenous women in Novel Gowok (1929). Gowok is a novel written by Liem Khing Hoo, depicting a relationship of race and gender under colonial discourse. To pursue the aim of this study, postcolonial feminist approach was used to reveal the quality of ideological and political relation under colonial discourse. The data collected were focussed on the relationship of women and race in this novel, the social group consciousness of the author, and colonial discourse. The results showed two points. First, the narrative of the indigenous women in this novel reflected the voice of Chinese-Indonesia descents from the moderate social group based on racial and gender relation. Second, the relationship of the indigenous women and the Chinese-Indonesia descents could be considered as political and ideological relation to realize tradition or culture nationalism concept in colonial contexts. In conclusion, this concept brings ambiguity characters.